The curious feminist : searching for women in a new age of empire - Enloe, Cynthia H., 1938- (University of California Press, 2004)
In this collection of lively essays, Cynthia Enloe makes better sense of globalization and international politics by taking a deep and personal look into the daily realities in a range of women's lives. She proposes a distinctively feminist curiosity that begins with taking women seriously, especially during this era of unprecedented American influence.
Keywords: Feminism.; Sex role.; Women and the military.; Women and war.; Feminism; Gender Role; Féminisme.; Rôle selon le sexe.; Femmes et armée.; Femmes et guerre.; feminism.; sex role.; SOCIAL SCIENCE -- Feminism & Feminist Theory.; SOCIAL SCIENCE -- Gender Studies.; Sex role; Women and the military; Women and war; Feminisme.; american influence.; anthropology.; compassion.; essay collection.; female authors.; feminist consciousness.; gender and sexuality.; gender norms.; gender studies.; global economy.; global politics.; globalization.; international politics.; international relations.; interviews.; masculinity.; modern empire.; modern feminists.; nonfiction.; oppressed groups.; pay attention.; praise.; privilege.; question.; social science.; social theory.; wartime.; women and gender.; women.; womens lives.; world cultures.